Azerbaijan Republic : Staff Report for the 2001 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Azerbaijan's 2001 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility (PRGF), and Request for Waiver of Performance Criteria. Economic and financial performance was satisfactory, and all quantitative performance criteria were met. Implementation of structural reforms was somewhat slower than programmed, and the authorities are requesting waivers for nonobservance of three structural performance criteria for end-September 2001 and the continuous performance criterion on the stock of external arrears. The adoption of regulations on the oil fund budget was done on time.